Activity profiles and physical demands of elite women's water polo match play - Tan, F.; Polglaze, T.; Dawson, B. (Journal of Sports Sciences, 2009)
The aim of this study was to quantify the movement patterns of contemporary elite women's water polo match play. Thirty-three player matches (centre, n = 15 and perimeter, n = 18) were analysed using video-based time-motion analysis. Frequency and duration of individual movements and distance swum were assessed. Mean match time and playing time were 69:48 ± 04.30 min:s and 33:14 ± 14:40 min:s, respectively. Players performed 330 ± 158 discrete movements per match, representing a change in movement every 6.2 s. There were 54 ± 25 high-intensity activities per match, or one every 38.4 s. These findings characterise women's water polo as a high-intensity intermittent sport. Total distance swum per match was 699.3 ± 296.8 m. Positional differences showed a predominance of wrestling in centre players (4:13 vs. 1:53 min:s; P < 0.001) and sprint swimming in perimeter players (2:09 vs. 0:52 min:s; P < 0.001). Players performed 6.7 ± 3.5 repeated high-intensity activity bouts per match, suggesting that this facet of play is important in water polo. Overall, exercise intensity decreased as a match progressed, suggesting the likelihood of fatigue during the latter stages. These findings provide important information for the planning and monitoring of training in women's water polo.